Descriptions, records, and key to the Hydrometra Latreille, 1796 (Hemiptera: Heteroptera: Hydrometridae) from Colombia - Martínez, David Camilo; Galindo-Malagón, Ximena Alejandra; Molano, Fredy; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2019)
Hydrometra colombiana Martínez and Galindo-Malagón, sp. nov., H. tayrona Martínez and Galindo-Malagón, sp. nov., and H. quimbaya Martínez and Galindo-Malagón, sp. nov. are described and compared with congeners. Furthermore, the female of H. williamsi Hungerford & Evans, 1934 and the male of H. adnexa Hungerford & Evans, 1934 are described. New records from Colombia and a key to the species of Hydrometra Latreille, 1796 recorded from the country are presented.